Potentially Inappropriate Medications and Potential Prescribing Omissions in Elderly Patients Receiving Post-Acute and Long-Term Care: Application of Screening Tool of Older People’s Prescriptions/Screening Tool to Alert to Right Treatment Criteria - Candeias, Catarina; Gama, Jorge; Rodrigues, Márcio; Falcão, Amílcar; Alves, Gilberto (Frontiers in Pharmacology, 2021)
Background: STOPP (Screening Tool of Older People’s Prescriptions) and START (Screening Tool to Alert to Right Treatment) criteria have been used to detect potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs). These criteria were applied to geriatric Portuguese patients receiving post-acute and long-term care to assess the prevalence and predictors of PIMs and PPOs. Methods: An observational, retrospective, cross-sectional and multicenter study was performed in 161 patients (aged ≥ 65 years) from eight Units for Integrated Continuous Care. Results: In these studied patients (mean age: 81.6, 64% female, median number of medications: 9) PIMs were detected in 85.1% and PPOs in 81.4% of patients. While PIMs mainly involved the central nervous system and psychotropic drugs (66.5%), PPOs were mostly related to musculoskeletal system (55.3%) and cardiovascular (39.8%) system. A subsequent analysis with logistic regression found the female gender, the hospital provenience, and the number of medications as predictors of PIMs. Predictors of PPOs were the Charlson Comorbidity Index and history of recent fractures. Conclusions: PIMs and PPOs were highly prevalent in the studied patients receiving post-acute and long-term care in Units for Integrated Continuous Care. Therefore, STOPP/START criteria might be an effective tool for improving prescribing quality and clinical outcomes in these frail elderly patients.